Juritraductology and the Right to Translation - Marta Sobieszewska (Facta Simonidis)
In the context of globalization, understood as a long-term historical process, issues of multilingualism and multiculturalism are becoming increasingly intertwined with access to justice. Within the European Union (EU), member states must respond to specific challenges related to citizen mobility within the Union and the influx of immigrants and refugees from outside it. Against this background, an analysis of Polish law reveals a clear deficit of regulations concerning the right to translation. From the perspective of legal certainty and transparency standards, this presents a highly undesirable situation. The article addresses issues related to the right to interpreter assistance for non-native speakers in a procedural context. The analyzed issues will be presented in relation to juritraductology (juritraductological approach to the translation of legal texts), a scientific discipline developed at the Centre de recherche interdisciplinaire en juritraductologie (Cerije) in Paris.